THE EFFECT OF USING VOICE OVER TECHNIQUE ON STUDENTS’ SPEAKING ABILITY - Juliana Juliana; Armia Dewi Pohan (Journal MELT (Medium for English Language Teaching), 2022)
This research was aimed to find the empirical evid of the effect of Using Voice Over Technique on students’ speaking ability. The method of this research was a quantitative method. The design of this study was experimental research. This study was conducted in SMK Sinar Husni Medan. The sample of this research was 60 students of twelfth grade. The instrument of this research was tests. The tests were divided into two, they were pre-test and post-test. The data were obtained from the tests and analyzed by using SPSS 25 program. The result of the research showed that the mean score of post test in control class was 64,67 while the mean score of post-test in experimental was 82,2. Based on the criteria of hypothesis test that if sig. 2 tailed (p) was lower than alpha (α) 0.05, then Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. In this research, the result of sig. 2 tailed was 0,000 and it proved that p <α. The result of Questionnaire showed 90% students said that Voice Over Technique can improve student's speaking ability.  Therefore, it proved that The Use of Voice Over Technique can improve student's speaking ability.